2007
DOI: 10.1007/s10661-006-9583-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Life Stage Fall Chinook Salmon Exposed to Hexavalent Chromium from a Contaminated Groundwater Source

Abstract: We conducted a laboratory evaluation to assess the risk to early life stage (i.e., eyed egg to swim up) fall Chinook salmon (Oncorhynchus tshawytscha) for exposure to hexavalent chromium from a contaminated groundwater source. Local populations of fall Chinook salmon were exposed to Hanford Site source groundwater that was diluted with Columbia River water. Specific endpoints included survival, development rate, and growth. Tissue burdens of fish were also measured to estimate uptake and elimination rates of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The tangible outcome of the project, which required over 5 years to complete, was a report to DOE laying out our findings (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The main findings were that: (1) salmon life cycles are varied and complex (involving spring and fall runs, Healey, 1991), (2) having good population estimates by species and runs is critical (Hyun et al., 2012a,b), (3) several species of salmon spend a significant part of their life cycle in the Columbia River (and mainly in the Hanford Reach) where they spawn (Hayes et al., 2013), (4) contaminants are not viewed generally by the State or DOE as a significant stressor on salmon, especially compared to other stressors (CRESP, 2015; NRC, 1996; Regetz, 2003; Tiller et al., 2004), (5) laboratory experiments indicated that there is a great deal of variability in results, no effects were found at Hanford‐relevant chromium exposures on fertilization, hatching, and exposure of alevins (early stage on salmon), but there were some laboratory effects of chromium on later stages of fry (Farag et al., 2006a,b; Patton et al., 2007), and (6) at some periods of time the fry may be vulnerable to chromium if they remain near the gravel surface where the pore water and river water meet (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The Tribes, however, remained concerned about potential long‐term effects of contaminants on eggs and fry of salmon (especially the DNA, R. Jim, Nov. 2014).…”
Section: Hanford Site As a Case Study: Multiple Ecologicies Stakehold...mentioning
confidence: 99%
“…The tangible outcome of the project, which required over 5 years to complete, was a report to DOE laying out our findings (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The main findings were that: (1) salmon life cycles are varied and complex (involving spring and fall runs, Healey, 1991), (2) having good population estimates by species and runs is critical (Hyun et al., 2012a,b), (3) several species of salmon spend a significant part of their life cycle in the Columbia River (and mainly in the Hanford Reach) where they spawn (Hayes et al., 2013), (4) contaminants are not viewed generally by the State or DOE as a significant stressor on salmon, especially compared to other stressors (CRESP, 2015; NRC, 1996; Regetz, 2003; Tiller et al., 2004), (5) laboratory experiments indicated that there is a great deal of variability in results, no effects were found at Hanford‐relevant chromium exposures on fertilization, hatching, and exposure of alevins (early stage on salmon), but there were some laboratory effects of chromium on later stages of fry (Farag et al., 2006a,b; Patton et al., 2007), and (6) at some periods of time the fry may be vulnerable to chromium if they remain near the gravel surface where the pore water and river water meet (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The Tribes, however, remained concerned about potential long‐term effects of contaminants on eggs and fry of salmon (especially the DNA, R. Jim, Nov. 2014).…”
Section: Hanford Site As a Case Study: Multiple Ecologicies Stakehold...mentioning
confidence: 99%
“…Such effects clearly demonstrate concentration-duration relations. The early life stage of Chinook salmon ( Oncorhynchus tshawytscha ) exposed to Cr(VI) (0 to 260 μ L −1 ) from a contaminated groundwater source was evaluated for 98 days /51/. The study revealed no significant changes in the survival rate, development, and behavior.…”
Section: Chromium Toxicity To Fishmentioning
confidence: 99%
“…Thus, there is an urgent need for removal of chromium and other metals from treated wastewater. Environmental impact of tannery effluents on plant and animal kingdom has been extensively studied (Somanath 2002;Upreti et al 2004;Shanker et al 2005;Patton et al 2007). The phytotoxic impact of these heavy metals was observed on crops such as cabbage, waterchestnut, tomatoes, chillies, rice, etc.…”
Section: Heavy Metals In Treated Effluentmentioning
confidence: 99%